问题 解答题
解方程(组)
(1)2x+4(2x-3)=6-2(x+1)
(2)
x-y+z=-1
5x+2y-z=6
4x-3y+2z=-5

(3)
2(3x-1)=3+3y
3x-1=2y
答案

(1)2x+4(2x-3)=6-2(x+1)

2x+8x-12=6-2x-2,

10x+2x=4+12

12x=16,

x=

4
3

(2)

x-y+z=-1    ①
5x+2y-z=6    ②
4x-3y+2z=-5   ③

①+②得:

6x+y=5,④

②×2+③得:

14x+y=7 ⑤,

⑤-④得:8x=2,

x=

1
4

把x=

1
4
代入④得:

y=

7
2

把x=

1
4
,y=
7
2
代入①得:z=
9
4

则原方程的解是:

x=
1
4
y=
7
2
z=
9
4

(3)

2(3x-1)=3+3y
3x-1=2y

原方程变形为:

6x-3y=5  ①
3x-2y=1  ②

①×2-②×3得:

3x=7,

x=

7
3

把x=

7
3
代入①得:y=3,

则原方程的解是;

x=
7
3
y=3

单项选择题
填空题 案例分析题